Implementasi SP4N-LAPOR terhadap Kualitas Pelayanan Publik di Kelurahan Dadok Tunggul Hitam, Kota Padang - Arni A; Lathifah Irbah; Rahma Ananda; Rahmat Aidil Fitrialdi; Yulia Hanoselina; Yuliarti Y (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study was motivated by the fact that public services remain less than optimal, particularly in managing public complaints and aspirations at the village administration level. Various issues are frequently encountered, including delayed government responses, limited transparency, and difficulties faced by citizens in accessing complaint-reporting mechanisms. The purpose of this study is to examine the implementation of the SP4N-LAPOR policy as an effort to improve the quality of public services in Dadok Tunggul Hitam Village, Padang City. This research employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews, direct observation, and documentation studies. The findings indicate that the implementation of SP4N-LAPOR has contributed positively to accelerating complaint handling and enhancing transparency in public grievance management. However, several challenges remain, including low public awareness, limited human resource capacity, and insufficient dissemination of information. Therefore, strengthening the competence of public service personnel and intensifying public outreach efforts are essential steps toward optimizing the quality of public services.